Poetry in the classroom: dialogic methodologies for the teaching of the literatures of São Tomé and Brazil - Nascimento, Rafaela Menezes Melo; Queiroz, Amilton José Freire de (The ESPecialist, 2024)
This work analyzes, from a decolonial perspective, a poetics of contemporary female Negritude. Where, the poem is proposed as a horizon for the reception and circulation of black diasporas, to expand the possibilities of approaching São Tomé and Afro-Brazilian literature in the classroom. As a corpus of analysis, we have “Voice - women” by Conceição Evaristo (2017) and “dark corner to the roots” by Conceição Lima (2006). Poems, whose lyrical, dramatic and symbolic dimension map a writing of the body and cross-border itineraries with distended poetic images, unveiling an intertextual, intercultural and intersemiotic mosaic of the voices of blackness today. To examine this issue, we adopted the reflections of Amâncio (2023) Ballestrin (2013) Bernd (2010), Candido (2006), Cosson (2009), Duarte (2011), Figueiredo (2013), Goulart (2022), Mignolo (2003) and Walsh (2013). Furthermore, didactic-methodological proposals emerge that address anti-racist education through Afro-descendant Literature, highlighting a lyrical self that weaves diasporas, memories, traditions and knowledge, giving a voice to black women in the family, social and literary sphere.